Evaluation of an electronic system for monitoring dairy cow rumination in a grazing-based system - Kappes R.* (2021)
© 2021, The Author(s), under exclusive licence to Springer Nature B.V.This research aimed to compare the rumination time estimated by an electronic monitoring system with direct visual observations of the rumination of dairy cows in a grazing-based system. Also, it aimed to estimate the agreement between different time intervals of the direct visual observations. To that end, we have observed twelve lactating cows for 16 h a day for 11 days. Then, we compared the data provided by the HealthyCow24® software with the visual observations to use as reference. After that, we estimated the Pearson’s correlation coefficients, the linear regression, and the Bland–Altman plot by using the SAS software. Results showed that the rumination data estimated by the HealthyCow24® software and the visual observations were highly correlated (0.81; P < 0.0001). In the Bland–Altman analysis, we observed that the average of the standard deviations between the visual observation and the electronic monitoring system was − 2.14 min during a 2-h period. The upper limit (95%) was 30.61 min/2 h and the lower limit (95%) was − 34.88 min/2 h. Moreover, visual observations at intervals of up to 15 min were correlated with the data estimated by the electronic monitoring system and observed at 5-min intervals. In conclusion, the Allflex SCR electronic monitoring system is efficient in measuring the rumination time of grazing cows. Also, direct visual observations with intervals no longer than 15 min are reliable when used for evaluating the behavior of cows without losing data accuracy.